The Effect of Attitudes Toward Spouse Selection and Mate Selection Criteria on Marital Stability Among Married Women Referring to Counseling Centers in Tehran - Balali, Marzieh; Goudarzi, Mahmoud; Dokaneifard, Farideh (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to examine the effect of attitudes toward spouse selection and mate selection criteria on marital stability among married women referring to counseling centers in Tehran. This applied, quantitative study employed a descriptive–correlational design using structural equation modeling. The statistical population consisted of all married women referring to licensed counseling centers in Tehran in 2023. A sample of 354 participants was selected based on the number of observed variables and a coefficient of 15 per variable, using a combination of cluster selection of counseling centers and convenience sampling of clients. Inclusion criteria included a minimum of three years of marriage, age range of 35–55 years, at least one child, and a minimum middle school education. Data were collected using the Attitudes Toward Mate Selection Questionnaire, the Attitudes Toward Marriage Questionnaire, and the Marital Instability Questionnaire. Data analysis was conducted using SPSS version 26 and AMOS version 23. Structural equation modeling results indicated that attitudes toward spouse selection had a positive and statistically significant direct effect on marital stability (β = 0.48, p < .001), whereas mate selection criteria had a negative and statistically significant direct effect on marital stability (β = −0.40, p < .001). Pearson correlation analyses further revealed significant associations between marital stability and pessimistic, optimistic, realistic, and idealistic attitudes toward marriage, as well as significant relationships between attitudes toward love and multiple components of marital attitudes. The findings suggest that positive, realistic, and flexible attitudes toward spouse selection enhance marital stability, while reliance on restrictive and rigid mate selection criteria undermines it, highlighting the critical role of pre-marital cognitive frameworks in long-term marital outcomes among married women.